Cognitive functions and white matter lesions on magnetic resonance images in a sample of normal Iranian population with cardiovascular risk factors. Issue 2 (April 2019) - Ashrafi, Farzad; Taheri, Morteza Sanei; Farzaneh, Aida; Behnam, Behdad; Ahmadi, Mehran Arab
Purpose: Due to a suggestive three-way relationship between brain structural disorders, microvascular lesions, and cognitive impairments, we aimed to examine the association of the volume and number of white matter hyperintensity lesions and lacunar infarcts with cognitive impairment among patients with cardiovascular risk factors in a sample of the Iranian population. Materials and methods: This study was conducted on a total number of 156 normal subjects aged 30–74 years with cardiovascular risk factors. We used the Framingham general cardiovascular risk factors prediction model to calculate the likelihood of each risk factor. The total number of lacunar infarcts and the volume of white matter hyperintensity lesion were calculated in brain magnetic resonance imaging. Cognition status was assessed using the Montreal Cognitive Assessment questionnaire. Results: An adverse association was revealed between Montreal Cognitive Assessment score and different cardiovascular risk profiles including the Framingham body mass index score ( p  < 0.001) and the Framingham lipid score ( p  < 0.001). The total volume of white matter hyperintensity was negatively associated with total Montreal Cognitive Assessment cognition score ( p  < 0.001). Our study also showed an adverse association between total number of lacunar infarcts and total Montreal Cognitive Assessment cognition score ( p  = 0.038) and with some cognition components including memory ( p  = 0.013), attention ( p  = 0.037), abstraction ( p  = 0.046), and orientation ( p  = 0.002). Conclusion: Periventricular lesions are associated with impaired memory, language, and visuoconstruction while subcortical lesions are associated with impairment in naming, attention, language, and abstraction functions in normal subjects with cardiovascular risk factors but without cardiovascular or cerebrovascular disorders.